Construction of a river buffalo (Bubalus bubalis) whole-genome radiation hybrid panel and preliminary RH mapping of chromosomes 3 and 10 - Amaral, M. E.J. [UNESP]; Owens, K. E.; Elliott, J. S.; Fickey, C.; Schäffer, A. A.; Agarwala, R.; Womack, J. E. (Taylor & Francis, 2007)
The buffalo (Bubalus bubalis) not only is a useful source of milk, it also provides meat and works as a natural source of labor and biogas. To establish a project for buffalo genome mapping a 5,000-rad whole genome radiation hybrid panel was constructed for river buffalo and used to build preliminary RH maps from two chromosomes (BBU 3 and BBU10). The preliminary maps contain 66 markers, including coding genes, cattle ESTs and microsatellite loci. The RH maps presented here are the starting point for mapping additional loci, in particular, genes and expressed sequence tags that will allow detailed comparative maps between buffalo, cattle and other species to be constructed. A large quantity of DNA has been prepared from the cell lines forming the RH panel reported here and will be made publicly available to the international community both for the study of chromosome evolution and for the improvement of traits important to the role of buffalo in animal agriculture.
Keywords: Gene mapping; Radiation hybrid panel; River buffalo; Whole genome